Erratum to: “The use of whole genome amplification for genomic evaluation of bovine embryos” - K. S. Pantiukh; I. V. Rukin; S. M. Portnov; A. Khatib; S. L. Panteleev; A. M. Mazur (Вавиловский журнал генетики и селекции, 2019)
.